Investigation on water droplet receding height impacting onto heated carbon surface - Illias, Suhaimi; Hussain, Suhaila; Ishak, Mohamad Shaiful Ashrul; Mustaffa, Mohammad Taufiq; Ismail, Khairul Azwan; Selamat, Salsuwanda; Ani, Mohd Hanafi (The Scientific Press, 2021)
This study investigates the receding water droplet height upon impact on a high temperature carbon surface in the film boiling regime. A 30.0-mm-diameter carbon disc with a height of 8.0 mm was used as the test surface due to its relativity low thermal conductivity compared to the more commonly studied alloy materials. For the water droplet, the diameter and temperature was constant at approximately 4.0 mm and 16.0 °C, respectively. The water temperature was maintained at the required temperature by circulating tap water into the droplet dispenser system. Meanwhile, the impact height was set at 65.0 mm which corresponds to a theoretical impact velocity of 1.129 m/s. A high speed video camera capable of capturing images at 10,000 fps was used to capture the impacting process. From the results obtained, it was found that the experimentally measured residence time was in good agreement with that calculated based on theory. Another important finding from the study was that the surface temperature had no significant effect to the changes in the water droplet height upon impact on the hot carbon surface.